2022
DOI: 10.3390/diagnostics12092052
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Abdominal Ultrasonography (POCUS) on the Way to the Right and Rapid Diagnosis

Abstract: Point-of-Care ultrasound (POCUS) is based on target ultrasound that is performed wherever a patient is being treated, and by a non-radiologist directly involved in the patient’s care. It is used either for quick diagnosis or procedural guidance. Abdominal pain is one of the most common complaints in emergency departments, and POCUS can help in the differentiation of patients who need additional diagnostic tests or hospital treatment, which eventually reduces the overall costs of health care. POCUS has high sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 140 publications
0
7
0
1
Order By: Relevance
“…The most common POCUS applications of abdominal ultrasounds include the evaluation of patients with abdominal pain or trauma [62,63]. Moreover, POCUS has also been recently used to estimate patients' fluid status, especially in those with acutely decompensated heart failure and acute kidney injury.…”
Section: Point-of-care Abdominal Ultrasoundmentioning
confidence: 99%
“…The most common POCUS applications of abdominal ultrasounds include the evaluation of patients with abdominal pain or trauma [62,63]. Moreover, POCUS has also been recently used to estimate patients' fluid status, especially in those with acutely decompensated heart failure and acute kidney injury.…”
Section: Point-of-care Abdominal Ultrasoundmentioning
confidence: 99%
“…Gastric ultrasound is increasingly used to assess gastric emptying in anesthesia and intensive care [33][34][35]. Some development is also reported in point-of-care ultrasound assessment of certain intestinal pathologies and abdominal venous congestion [36,37]. One study reported assessment of enteral feeding intolerance with measuring gastric antrum, colonic diameter and peristaltic frequency [38], while standardized protocol for gastrointestinal ultrasound in critical illness is still lacking [39].…”
Section: Key Pointsmentioning
confidence: 99%
“…POCUS allows the physician to review and interpret images and make critical decisions at the point of care, and many studies have shown that POCUS protocols significantly reduced diagnostic time[ 4 ], decrease procedure complications[ 5 ], improves patient safety, increased success rates of invasive bedside procedures[ 6 ], and minimize delays in care such as time to obtain antibiotics or time to move into surgery[ 7 ].…”
Section: Introductionmentioning
confidence: 99%